(untitled) (The Pakistan Development Review, 2007)
Drinking water is the basic need of human life. Safe drinking water is an essential component of primary health care and have vital role in poverty alleviation. There is positive correlation between increased national income and the proportion of population with access to improved water supply. An increase of 0.3 percent investment in household access to safe drinking water generates one percent increase in GDP. Whereas, provision of safe drinking water supply is an effective health intervention reduces the mortality caused by water-borne diseases by an average 70 percent. Inadequate drinking water not only resulted in more sickness and deaths, but also augments health costs, lower worker productivity and school enrolment [World Bank (1994)]. The World Health Organisation (WHO) estimate 1.8 million people in developing countries die every year from diarrhea and cholera, Out of these 90 percent are children under the age of five years. While 88 percent of diarrhoeal diseases are attributed to unsafe water supply, inadequate sanitation and hygiene [WHO (2004)]. The situation is not very different in Pakistan; the access to safe drinking water is estimated to be available to 23.5 percent of population in rural areas and 30 percent in urban areas. While every year 0.2 million children die due to diarrhoeal diseases [Rosemann (2005)].